Mecz tenisowy Piast Gliwice - S.K.T. Sopot. (Gdynia : [s.n.], 1948)
Afisz inf. o zawodach, które odbyły się na kortach SKT Sopot 5-6.06.1948 r.
Keywords: Tenis -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- źródła